2003
DOI: 10.1161/01.hyp.0000069260.11830.cd
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine-Mediated Inhibition of Renal Na,K-ATPase Is Reduced by Insulin

Abstract: Recently we have reported that rosiglitazone treatment of obese Zucker rats reduced plasma insulin and restored the ability of dopamine to inhibit Na,K-ATPase (NKA) in renal proximal tubules. The present study was performed to test the hypothesis that a chronic increase in levels of insulin causes a decrease in expression of the D1 receptor and its uncoupling from G proteins, which may account for the diminished inhibitory effect of dopamine on NKA in obese Zucker rats. We conducted experiments in primary prox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 52 publications
2
29
0
Order By: Relevance
“…However, endogenous renal dopamine production is normal or even increased in obese humans (46), monkeys (43), and rats (39). Therefore, the dopaminergic defect in the obese male rat has been suggested to be at the receptor or postreceptor level (4,5,7,23,24,40). Our finding of decreased renal expression of D1R in obese male rats provides a potential explanation for the reduced D1-like dopaminergic signaling previously reported in the proximal tubule of these rats (5,31).…”
Section: Discussionmentioning
confidence: 50%
“…However, endogenous renal dopamine production is normal or even increased in obese humans (46), monkeys (43), and rats (39). Therefore, the dopaminergic defect in the obese male rat has been suggested to be at the receptor or postreceptor level (4,5,7,23,24,40). Our finding of decreased renal expression of D1R in obese male rats provides a potential explanation for the reduced D1-like dopaminergic signaling previously reported in the proximal tubule of these rats (5,31).…”
Section: Discussionmentioning
confidence: 50%
“…In proximal tubular cell culture insulin is shown to down regulate the dopamine D 1 receptors and cause uncoupling of D 1 receptors from G proteins (9). Several groups have suggested that hyperinsulinemia may lead to an increase in sodium reabsorption (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…Primary cell cultures grown in 12-well plates were used for 86 Rb uptake measurement according to our published method (5). The cells were incubated without or with SKF-38393 for 10 min at 37°C.…”
Section: Methodsmentioning
confidence: 99%